Impact of motor education levels and circuit training on enhancing wrestling techniques among adolescent athletes - Juhanis,; Iskandar,; Endrawan, I Bagus; S, Adi; Santoso, Slamet (Journal Sport Area, 2024)
Background Problems: Wrestling is a compulsory course that can improve physical strength, discipline, and strategic skills and student learning outcomes. However, the learning outcomes are still not optimal due to inconsistent training, limited technique understanding, and a lack of independent training opportunities. Research Objectives: The purpose of this study is to evaluate the effect of motor education level and circuit training on proficiency in learning wrestling martial arts techniques. Methods: This study used an experimental design with a pretest-posttest control group where there are two groups, the high motor ability group and the low motor ability group. The population consists of 40 students, and a sample of 20 students was selected using purposive sampling techniques based on certain criteria. Motor ability in this study is defined as an individual's ability to learn and develop motor skills, which is used to measure how quickly and efficiently a person can learn new motor movements. Data collection was done by measuring the level of motor ability and evaluating the techniques of wrestling after a period of practice. Data analysis was conducted using SPSS 23 statistical software to evaluate the learning outcomes of the basic techniques of wrestling. Findings/Results: The results of the data analysis showed that overall, there were no significant differences between the two groups. However, when looking closely at the level of motor skills, there are differences in the post-test scores between students with high and low motor skills. Conclusion: The conclusions of the study showed that although there were no significant differences between the two groups, the high motor skills group showed more consistent improvements. Future research could focus on the development of physical and mental skills such as endurance, strength, and discipline, which are important in improving wrestlers’ performance.